Technology and Its Application in Marketing: Some Insights - V., Ranjith P.; Arvind, Tripti; Upadhyaya, Bhargavee (Journal of International Conference Proceedings, 2023)
Information technology and its advancement is helping the growth of service and relationship building among marketers and it changes the way marketing managers do their job. The use of online, websites, online contests, and promotions, etc. are making the marketing concept very challenging. Concepts like quality function deployment and Kansei engineering are used widely to understand customer needs and to translate them into product design. Also, the availability of Computer-Generated Imagery (CGI) offers a smart alternative for marketers who are focusing on the cost benefits of various marketing solutions. The growth of digital marketing is only set to continue and new technologies such as advances in CGI can dramatically cut the cost of creating advertising campaigns. Different quality concepts like quality function deployment, Just in Time, etc. utilize technology and modern computer software to improve marketing solutions. The study is an attempt to find out the uses of these technological advancements in marketing using a secondary study approach and it is primarily an exploratory study to investigate various uses of modern technology, quality concepts and their applications.